Communications with Customers in the Service Industry: A Case of Service Sales Manual Development - Hwang, Hyemi; Kwon, Dohee (Business Communication Research and Practice, 2020)
Objectives:This study aims to introduce a development case of empirical service manuals utilized by service corporations and help service managers and leaders for their future effective management on moment of truth (MOT). Methods:In order to develop a duty-free service manual, the 2019 MOT monitoring evaluation, customer satisfaction survey, voice of customers, and a previous service manual developed in 2013 were analyzed. The requirements of executives and managers were taken into consideration. The service standards were set with the cooperation of subject matter experts, and the contents of the service manual were revised to reflect the opinions of employees. Results:The standard behaviors and guidelines at each stage of the sales process were organized, and the best cases for sales conversations were shared at the first and the second workshops. The developed service manual was distributed to the division managers and the sales directors, and training was provided for effective use of the manual. Conclusions:The developed manual is used for the employees to teach them about the service process and customer service skills during their customer satisfaction training and the new employee training. A developed service manual should be utilized by employees not only published as a booklet. In order to promote the implementation of service manuals in a real MOT, the continuous monitoring of employee’s behavior according to the service manual and immediate feedback on employee performance are required. KCI Citation Count: 1